1974
DOI: 10.3758/bf03203267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of noise letters upon the identification of a target letter in a nonsearch task

Abstract: During a I-sec tachistoscopic exposure, Ss responded with a right or left leverpress to a single target letter from the sets Hand K or Sand C. The target always appeared directly above the fixation cross. Experimentally varied were the types of noise letters (response compatible or incompatible) flanking the target and the spacing between the letters in the display. In all noise conditions, reaction time (RT) decreased as between-letter spacing increased. However, noise letters of the opposite response set wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

214
5,615
23
65

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 6,469 publications
(5,917 citation statements)
references
References 14 publications
214
5,615
23
65
Order By: Relevance
“…This idea is consistent with evidence from the attention literature that unattended or irrelevant stimuli are processed (e.g., Mack & Rock, 1998) and can compete for resources (Eriksen & Eriksen, 1974;Stroop, 1935). The results of Experiment 2 further localized this effect to the presence of two characters in the discourse rather than their visual presence in the scene being described.…”
Section: Discussionsupporting
confidence: 87%
“…This idea is consistent with evidence from the attention literature that unattended or irrelevant stimuli are processed (e.g., Mack & Rock, 1998) and can compete for resources (Eriksen & Eriksen, 1974;Stroop, 1935). The results of Experiment 2 further localized this effect to the presence of two characters in the discourse rather than their visual presence in the scene being described.…”
Section: Discussionsupporting
confidence: 87%
“…Participants completed congruent and incongruent conditions of the Eriksen flanker task (Eriksen & Eriksen, 1974), which required them to respond as quickly as possible to an array of letters presented on a computer monitor from a distance of 1 m with visual angles of 1.7° and 3.7° in the vertical and horizontal directions, respectively. The stimuli were 7.62-cm-tall white letters presented focally on a black background in a random order for 200 ms with an interstimulus interval of 1,200 ms from stimulus offset to onset.…”
Section: Cognitive Taskmentioning
confidence: 99%
“…However, the fuzziness lies in different parts of the system. Spacebased theories of attention assume that the boundary of the sampled region--the edge of the spotlight--is fuzzy (e.g., Eriksen & Eriksen, 1974;Eriksen & Hoffman, 1973). This idea is explicit in LaBerge and Brown's (1989) gradient theory.…”
Section: Extension O F C O D E To Attentionmentioning
confidence: 99%
“…High discriminability produces big spotlight beams and low discriminability produces small ones, consistent with the data and with theorists' speculations. Eriksen and Eriksen (1974) published an important article on which much of the debate over space-based and object-based attention was grounded. They showed that people were influenced by distractor items that flanked the target even when there was no uncertainty about target location.…”
Section: Z¢8mentioning
confidence: 99%